Management Strategy (4M) of the Ancient Chinese Chak-ngeaw Community Market by First-Order Confirmatory Factor Analysis - Saethow, Phannaphat; Kanjanawanawan , Sakda; Tongkaw, Anurak (Dusit Thani College Journal, 2020)
This research aimed to study the demographics and opinions of entrepreneurs regarding management in the Ancient Chinese Chak-ngeaw Community Market, Pattaya City and was analyzed using the first - order confirmatory factor of the management 4M theory in the Ancient Chinese Chak-ngeaw community market to develop management strategies based on 4M theory by mixed-method research. This research was a mixed-method, so-called Embedded-Correlational Design. The data was collected by multi-stage random sampling methods from 97 entrepreneurs consisting of 37 males and 60 females, and 10 structured interviews. The instruments were a questionnaire and structured interviews that consisted of content validity and reliability tests by Cronbach’s alpha coefficient of the questionnaire which was .92 and included an Investigator triangulation check. Research findings showed that the Ancient Chinese Chak-ngeaw community market, Pattaya City has good management, however, has room for improvement. The education level of entrepreneurs affected their opinions regarding the management 4M theory in the Ancient Chinese Chak-ngeaw community market, Pattaya City. The most important strategy of the Ancient Chinese Chak-ngeaw community market was the material component of 4M theory that will make this area more attractive.